Beyond Administrative Data: A Vision for Health Information Systems for Canada - Alan Katz, Louis Barré, Tom Fogg and Steven Lewis (Healthcare Policy, 2011)
The Manitoba Centre for Health Policy has achieved much success over the past 20 years in building an administrative claims data repository, using that data for innovative, policy-relevant research, and developing effective knowledge translation mechanisms. Researchers have long recognized the limitations of administrative data while working creatively to minimize these limitations using linkages and cutting-edge analytical techniques. We are, however, on the verge of a new era of data use in Canada. The Canadian Institute for Health Information (CIHI), Canada Health Infoway and federal, provincial and territorial ministries of health are collaborating on an initiative to inform the planning and development of health information systems across Canada to support a full spectrum of uses of data, including health research.